2018
DOI: 10.3390/ijms19113593
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Apolipoprotein B-Containing Lipoproteins through Endothelial Cells Is Associated with Apolipoprotein E-Carrying HDL-Like Particle Formation

Abstract: Passage of apolipoprotein B-containing lipoproteins (apoB-LPs), i.e., triglyceride-rich lipoproteins (TRLs), intermediate-density lipoproteins (IDLs), and low-density lipoproteins (LDLs), through the endothelial monolayer occurs in normal and atherosclerotic arteries. Among these lipoproteins, TRLs and IDLs are apoE-rich apoB-LPs (E/B-LPs). Recycling of TRL-associated apoE has been shown to form apoE-carrying high-density lipoprotein (HDL)-like (HDLE) particles in many types of cells. The current report studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Although one could argue that cord cells do not reflect the physiology of brain vasculature, we and others have previously demonstrated that HUVECs express BBB marker proteins when cocultured with astrocytes 11,54,55 . Further, we have demonstrated here that apoE is restricted in the abluminal chamber in our model; a feature characteristic of BBB EC, given that apoE is actively transported through peripheral ECs 56,57 . Another limitation is that we used primary cells for the vascular cells over iPSC-derived cells.…”
Section: Discussionsupporting
confidence: 50%
“…Although one could argue that cord cells do not reflect the physiology of brain vasculature, we and others have previously demonstrated that HUVECs express BBB marker proteins when cocultured with astrocytes 11,54,55 . Further, we have demonstrated here that apoE is restricted in the abluminal chamber in our model; a feature characteristic of BBB EC, given that apoE is actively transported through peripheral ECs 56,57 . Another limitation is that we used primary cells for the vascular cells over iPSC-derived cells.…”
Section: Discussionsupporting
confidence: 50%
“…These few examples clearly demonstrate that the simplified view on the rheostat of ceramide and S1P as pro-and anti-apoptotic balance will need to be replaced by a more mechanistically refined model invoking specific interaction with rafts and proteins regulating cell signaling pathways in neural development and disease. HDL, which is predominantly produced in the liver and intestine, lacks ApoB and is instead mainly accompanied by ApoA-I [150]. ApoE4, one of the 3 common isoforms of ApoE (E2, E3, and E4),…”
Section: Lipid Rafts and Binding To Distinct Proteins Determines The mentioning
confidence: 99%
“…ApoE is carried by chylomicrons, VLDL, and a subclass of HDL. HDL containing ApoE is formed when triglyceride-rich lipoproteins, such as VLDL and chylomicrons release fatty acids upon lipolysis [150]. Circulating ApoE4 prefers association with VLDL and chylomicrons, while ApoE3 prefers HDL [152].…”
Section: Extracellular Trafficking Of Sphingolipids and Effect On Blomentioning
confidence: 99%
“…The carrier apolipoprotein (Apo) of liver-derived lipoproteins, VLDL and LDL, is apoB100, while that of the lipoproteins of the intestine, chylomicrons, is apoB48. HDL, which is predominantly produced in the liver and intestine, lacks ApoB and is instead mainly accompanied by ApoA-I [155]. ApoE4, one of the 3 common isoforms of ApoE (E2, E3, and E4), is linked with a strongly increased risk of developing AD [156].…”
Section: Introduction Of Lipoproteinsmentioning
confidence: 99%
“…ApoE is carried by chylomicrons, VLDL, and a subclass of HDL. HDL containing ApoE is formed when triglyceride-rich lipoproteins, such as VLDL and chylomicrons release fatty acids upon lipolysis [155]. Circulating ApoE4 prefers association with VLDL and chylomicrons, while ApoE3 prefers HDL [157].…”
Section: Introduction Of Lipoproteinsmentioning
confidence: 99%